Awareness of Temporary Traffic Signs and Cellular Data Usage on Smart Phone: Ideas for Digital Safety Management - Mahasirikul, Narongdet; Aksorn, Preenithi (Local Administration Journal, 2021)
This research studied the relation between awareness toward temporary traffic signs in and smart phones’ cellular data usage. The sample was 600 drivers, divided into two group by their smart phones’ cellular data uses: drivers who used and those that did. Data were collected by questionnaires from visitors at the Land Transport Office in Khon Kaen. The results showed that the use of a smart phone’s cellular data has no effect on awareness of compliance with traffic signs, the characteristics of quality and standard traffic signs, the recommended speed in work zones, and the risk in a work zone. However, the use of a smart phone’s cellular data has an effect on awareness of the objectives and meanings of traffic signs and the importance and necessity of traffic sign installation. Further, the group of drivers who used their smart phone’s cellular data have a greater awareness of traffic signs in terms of the objectives and meanings and the importance and necessity of traffic sign installation more than the other group. A notable problem found was traffic signs that were installed in inappropriate positions. It was found that accidents in work zones could be reduced by adjusting the drivers’ behaviors. It is suggested that the audio system could be the most efficient platform of notification on smart phones and that digital technology could help to prevent accidents. Nevertheless, drivers must abide by traffic laws and regulations and must be conscious of hazards at all times.